2022
DOI: 10.21930/agrosavia.nbook.7405743
|View full text |Cite
|
Sign up to set email alerts
|

Guía para el establecimiento y manejo de la hierbabuena (Mentha spicata L.) en el Suroeste antioqueño

Abstract: Esta guía está dirigida especialmente a los productores del Suroeste antioqueño para la producción de hierbabuena (Mentha spicata L.) y muestra el paso a paso de los aspectos a tener en cuenta para su producción en campo, cosecha, poscosecha y agroindustria, a partir de un lenguaje sencillo e ilustrado con imágenes de las fincas donde se llevaron a cabo las diferentes actividades y capacitaciones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…found that the increase and yield of volatile compounds can be favored, which is closely related to the increase in biomass in plants treated with chemical fertilization. Franco et al (2022) reported that the most relevant nutrients in the cultivation of Mentha, in their order were N, K, Ca and Mg, being similar to what was found in this study. It should be noted that the excess of Zn presented antagonism with B, showing a differential when making foliar and/or edaphic applications with this element.…”
Section: Resultssupporting
confidence: 90%
“…found that the increase and yield of volatile compounds can be favored, which is closely related to the increase in biomass in plants treated with chemical fertilization. Franco et al (2022) reported that the most relevant nutrients in the cultivation of Mentha, in their order were N, K, Ca and Mg, being similar to what was found in this study. It should be noted that the excess of Zn presented antagonism with B, showing a differential when making foliar and/or edaphic applications with this element.…”
Section: Resultssupporting
confidence: 90%
“…Horciasisca signatus (Miridae), se convierte en el primer reporte asociado a cultivos de menta en el Oriente Antioqueño y posiblemente en Colombia, siendo un potencial insecto nocivo en el cultivo de menta para exportación, puesto que el follaje es la parte exportable de la planta (Franco et al 2022), y es en el tercio superior de ésta donde se observa el daño correspondiente unas manchas necróticas, síntoma denominado comúnmente como peca, el cual aparentemente es ocasionado por H. signatus al alimentarse (Figs. 2A, B), tal como lo menciona Silva et al (2017), que este tipo de manchas necróticas es característico del daño ocasionado por chinches fitófagos de la familia Miridae.…”
Section: Discussionunclassified